Global state regulation by output feedback for feedforward systems with input and output dependent incremental rate. Issue 6 (June 2015) - Jia, Xianglei; Xu, Shengyuan; Jiao, Ticao; Chu, Yuming; Zou, Yun
Abstract In this paper, the problem of global state regulation by output feedback is considered for a class of uncertain feedforward nonlinear systems with free-delay or time-delay states. Compared with existing results, we construct a novel observer-based controller with gain exponent to achieve the global state regulation via single output feedback under less conservative assumptions. Further, by using the Lyapunov–Krasovskii theorem, we show that the control scheme proposed is available to a class of time-delay systems with input and output dependent incremental rate. Finally, a numerical example is given to illustrate the usefulness of our results.